COVID-19 vaccine express strategy in Malawi: An effort to reach the un-reach. Issue 35 (19th August 2022) - Sethy, Ghanashyam; Chisema, Mike; Sharma, Lokesh; Joshi, Krupal; Singhal, Sanjay; Omar Nicks, Patrick; Macheso, Steve; Damte, Tedla; Eleonore Ba, Antoinette; Mitambo, Collins; Thomas, Mavuto; Laher, Beverly; et al.
Abstract: Objectives: To establish the impact of "Covid-19 Vaccination express" (CVE) on vaccine uptake in Malawi. Design: Retrospective cross-sectional study to compare the daily vaccine administration rate in CVE and routine covid vaccination (RCV). RCV data was collected from March 2021 to October 2021. The data regarding CVE was collected from 5 November 2021 to 31 December 2021. Data was collected regarding (1) the total number and type of vaccine doses administered and (2) Demographic details like age, gender, occupation, presence of comorbidities, the first dose, or the second dose of the people who received a vaccine. Results: From March-December 2021, a total of 1, 866, 623 COVID-19 vaccine doses were administered, out of which 1, 290, 145 doses were administered at a mean daily vaccination rate of 1854 (95 % CI: 1292–2415) doses as a part of RCV, and 576, 478 doses were administered at a mean daily vaccination rate of 3312 (95 % CI: 2377–4248) doses as a part of CVE. Comparing the mean daily doses (Astra Zeneca, AZ doses 1 & 2) administered in the CVE and RCV showed that the mean daily doses of AZ vaccine administered were significantly higher in the CVE (p < 0.05). Conclusion: CVE successfully increased the uptake of the Covid-19 vaccine.